Formulation Optimization Peel-Off Gel Mask Base of Red Rice Ethanolic Extract in Combination of HPMC and PVA using Factorial Design Method - Eka Wulansari; Agus Siswanto; Diniatik Diniatik (Jurnal Kefarmasian Indonesia, 2025)
In earlier research, red rice extract was shown to possess anti-oxidant, anti-inflammatory, anti-cancer, and anti-photoaging qualities. It was also shown to inhibit the degradation of collagen and hyaluronic acid (HA) in cutaneous fibroblast cells caused by sunlight. Red rice has been used for cosmetics for centuries, and its benefits have been applied to modern skin care products. It can be made as a peel-off gel mask to increase its practicality. The peel-off gel mask has the main ingredients of PVA as a film layer and HPMC as a gelling agent. This research is experimental research with extraction stages, DPPH assay, and gel formulations. Formula optimization was carried out through a Factorial Design method approach with a total of 12 formulas. The results of the evaluation of the physical properties of the red rice ethanol extract peel-off gel mask were processed using Design Expert software ver 13. The results of this study obtained an optimum formula with HPMC and PVA concentrate levels of 15.37% and 4.99%, respectively. The results of the physical evaluation of the red rice ethanol extract peel-off gel mask with the optimum formula obtained a pH of 5.89, a spread of 5.19 cm, and a drying time of 14.71 minutes. Keywords: Peel-Off Gel Mask; Factorial Design; HPMC; PVA